Capacidade física, função muscular e atividade de vida diária em pacientes com bronquiectasia - Camargo, Anderson Alves de (2013)
Introduction: Studies evaluating exercise capacity and pulmonary effects of bronchiectasis (BCQ) in adult patients are scarce. Objectives: Article 1- Analyze the reproducibility of two incremental step tests: Chester step test (CST) and modified incremental step test (MIST); article 2 - Investigate the reproducibility and validity of the incremental shuttle walking test (ISWT) and compare the exercise-induced desaturation between the ISWTI and cardiopulmonary exercise test (CPET) and article 3: evaluate the extrapulmonary features of BCQ on exercise capacity, peripheral muscle strength, physical activity in daily life (PADL) and health-related quality of life. Method: In the first study, 17 patients performed two CST, MIST and six-minute walk test (6MWT). In the second study, patients underwent two ISWT (same day), CPET and the number of steps (NS) was obtained from a pedometer. In article 3, 80 patients underwent the bioimpedance, ISWT, CPET, maximum voluntary contraction (MVC) of the biceps brachii (BB) and quadriceps femoris (QF), answered to the quality of life questionnaires of (SF-36 and Saint George Respiratory Questionnaire (SGRQ) and to the dyspnoea scale (Medical Research Council - MRC) and a pedometer recorded the NS. Results: Article 1 the number of steps was reproducible for the CST (124 ± 65 and 125 ± 67) and MIST (158 ± 83 and 156 ± 76). There was no difference in the variables between both tests at the peak exercise. The CST had significantly lower duration in comparison to MIST (6.1 ± 2.2 min and 8.8 ± 2.8 min) and lower number of steps (128 ± 64 and 166 ± 78). Article 2 the median distance in the ISWT-1 was 430 m (333-525 m) and 440 m (340-535 m) in the ISWT-2, with excellent intraclass correlation coefficient [0.995 (0.990-0.997)]. The ISWT induced higher desaturation than the CPET (P < 0.0001) with 23% of the patients showing desaturation only during the ISWT (P = 0.021). Article 3 - The patients showed reduced aerobic capacity (VO2: 81 ± 15 and 63 ± 13 % of predict), functional capacity (ISWT distance: 73 ± 15 and 52 ± 13 % of predict) and MVC QF (26 ± 11 kg and 22 ± 10 kg). Lower values of NS/day were observed in patients compared to controls (9,526 ± 5,843 and 12,009 6,031; P = 0.052) and for quality of life as well. Conclusion: The field tests, step tests and ISWT, are reproducible in patients with BCQ. The ISWT is more sensitive in detecting desaturation in this population. Patients with BCQ present reduced aerobic capacity, muscle strength of the QF, physical activity in daily life, and impairment of health-related quality of life.